(untitled) (Clinics, 2011)
OBJECTIVE: The goal of the present study was to estimate the risk ratio of herpes zoster among systemic lupus erythematosus patients after disease onset compared with a cohort of patients without systemic lupus erythematosus over a three-year period. METHODS: A nationwide population-based cohort study using the National Health Insurance Research Database identified 10,337 new cases of systemic lupus erythematosus as the study cohort. In addition, 62,022 patients without systemic lupus erythematosus, who were matched for age, gender, and date of systemic lupus erythematosus diagnosis, were used as the comparison cohort. These cohorts were followed-up for three years. A Cox proportional hazard regression was performed to estimate the risk ratio of herpes zoster, with adjustments for age, gender, level of insurance, urbanization level, geographic region, comorbid medical conditions, average daily dosage of corticosteroids, and the use of immune-modulation agents. RESULTS: Compared to patients without systemic lupus erythematosus, the crude risk ratio and adjusted risk ratio of herpes zoster among systemic lupus erythematosus patients were 7.37 (95% confidence interval 6.75-8.04) and 2.45 (95% confidence interval 1.77-3.40), respectively. Stratified by gender, the adjusted risk ratio of herpes zoster was 2.10 (95% confidence interval 1.45-2.99) in women and 7.51 (95% confidence interval 2.89-19.52) in men. Stratified by age, the adjusted risk ratio peaked in systemic lupus erythematosus patients who were aged 18 to 24 years (risk ratio 8.78, 95% confidence interval 3.08-24.97). CONCLUSION: Based on nationwide population-based data, there is an increased risk of herpes zoster in systemic lupus erythematosus patients compared with non-systemic lupus erythematosus patients, particularly among males and patients aged 18 to 24 years. Further research on the associated risk factors for herpes zoster in systemic lupus erythematosus patients is needed.